DAYA TERIMA DAN KANDUNGAN GIZI FORMULASI DIMSUM HATI AYAM DAN BAYAM SEBAGAI ALTERNATIF MAKANAN SELINGAN UNTUK PENCEGAHAN ANEMIA PADA REMAJA PUTRI - Azzah Abidah Azro; Fitria Dhenok Palupi; Juin Hadi Suyitno (JURNAL MEDIA KESEHATAN, 2025)
Anemia in adolescent girls has serious impacts, including the risk of stunting and maternal mortality, with prevalence steadily increasing from 2013 to 2018. This study aimed to analyze the nutritional quality and organoleptic properties of dim sum made from chicken liver and spinach as a snack to prevent anemia. The formulations consisted of P0 (control, 100% chicken meat), P1 (80:10:10), P2 (70:20:10), and P3 (60:30:10), using a completely randomized design (CRD) with three replications. The results showed that increasing the proportion of chicken liver and spinach enhanced the levels of iron, protein, energy, fat, and carbohydrates in the dim sum. Hedonic tests on taste, color, aroma, and texture revealed no statistically significant differences (p>0.05). The P3 formulation was identified as the best treatment and is recommended for anemia prevention.